Organizational Capability of Jasinga District, Bogor Regency in Development of Village Administration - Santoso, Santoso; Tukiran, Martinus; Rusliandy, Rusliandy; Juanda, Enda; Wardani, Peni Arianita (LPPM Universitas PGRI Sumatera Barat, 2023)
ABSTRACT The study aimed to analyze the organizational capabilities of the Jasinga District, Bogor Regency, in fostering the administration of village government with a broader scope of tasks and extensive budget management. The method is a descriptive qualitative approach with data collection techniques using interviews, observation, and literature studies. The analytical knife used is the concept of organizational capability put forward by Neo and Chan. The study's results stated that there were obstacles in the aspects of able people and agile processes, including limited staff, barriers to competency development, team member recruitment that could have used the merit system, substandard educational qualifications, and limited resources. This condition results in flawed thinking ahead, thinking again, and thinking across, which must be developed within the organization. The recommendations proposed are improving able people and agile processes by increasing educational qualifications, competency development programs, and merit system-based recruitment. Districts must also apply thinking ahead, thinking again, and thinking across in building dynamic organizational capabilities. Meanwhile, in the context of optimizing the development of village government administration, it is necessary to develop competence in the field of village administration for sub-district officials.